Diminished Peripheral CD29hi Cytotoxic CD4+ T Cells Are Associated With Deleterious Effects During SIV Infection - Olwenyi, Omalla A.; Johnson, Samuel D.; Pandey, Kabita; Thurman, Michellie; Acharya, Arpan; Buch, Shilpa J.; Fox, Howard S.; Podany, Anthony T.; Fletcher, Courtney V.; Byrareddy, Siddappa N. (Frontiers in Immunology, 2021)
Cytotoxic CD4+ T cells (CD4+ CTLs) limit HIV pathogenesis, as evidenced in elite controllers (a subset of individuals who suppress the virus without the need for therapy). CD4+ CTLs have also been shown to kill HIV-infected macrophages. However, little is known about their contribution towards HIV persistence, how they are affected following exposure to immune modulators like morphine, and what factors maintain their frequencies and function. Further, the lack of robust markers to identify CD4+ CTLs in various animal models limits understanding of their role in HIV pathogenesis. We utilized various PBMC samples obtained from SIV infected and cART treated rhesus macaques exposed to morphine or saline and subjected to flow cytometry evaluations. Thereafter, we compared and correlated the expression of CD4+ CTL-specific markers to viral load and viral reservoir estimations in total CD4+ T cells. We found that CD29 could be reliably used as a marker to identify CD4+ CTLs in rhesus macaques since CD29 hi CD4+ T cells secrete higher cytotoxic and proinflammatory cytokines following PMA/ionomycin or gag stimulation. In addition, this immune cell subset was depleted during untreated SIV infection. Strikingly, we also observed that early initiation of cART reconstitutes depleted CD29hi CD4+ T cells and restores their function. Furthermore, we noted that morphine exposure reduced the secretion of proinflammatory cytokines/cytotoxic molecules in CD29 hi CD4+ T cells. Lastly, increased functionality of CD29 hi CD4+ T cells as depicted by elevated levels of either IL-21 or Granzyme B hi/ T Bet+ gag specific responses were linked to limiting the size of the replication-competent reservoir during cART treatment. Collectively, our data suggest that CD4+ CTLs are crucial in limiting SIV pathogenesis and persistence.